Traditions of Classical Music - Nishanova Nargiza (Researchparks Publishing, 2021)
A high example of our classical music is the perceptions about the forms of percussion, action, pattern, such status in the instrumental and singing tracks of the Masterpiece, which are mentioned in detail. Music treatises of music scientist Kavkabi Bukhari, XVII century mature artist Darvish Ali Changi and other authors, who lived and worked in the XVI century, were published.